In Vivo Bioluminescence Imaging of Cell Differentiation in Biomaterials: A Platform for Scaffold Development. - Bagó, Juli R; Aguilar, Elisabeth; Alieva, María; Soler-Botija, Carolina; Vila, Olaia F; Claros-Gil, Silvia; Andrades-Gómez, José Antonio; Becerra-Ratia, José; Rubio, Nuria; Blanco, Jerónimo (Mary Ann Liebert, 2012)
In vivo testing is a mandatory last step in scaffold development. Agile longitudinal noninvasive real-time monitoring of stem cell behavior in biomaterials implanted in live animals should facilitate the development of scaffolds for tissue engineering. We report on a noninvasive bioluminescence imaging (BLI) procedure for simultaneous monitoring of changes in the expression of multiple genes to evaluate scaffold performance in vivo. Adipose tissue-derived stromal mensenchymal cells were dually labeled with Renilla red fluorescent protein and firefly green fluorescent protein chimeric reporters regulated by cytomegalovirus and tissue-specific promoters, respectively. Labeled cells were induced to differentiate in vitro and in vivo, by seeding in demineralized bone matrices (DBMs) and monitored by BLI. Imaging results were validated by RT-polymerase chain reaction and histological procedures. The proposed approach improves molecular imaging and measurement of changes in gene expression of cells implanted in live animals. This procedure, applicable to the simultaneous analysis of multiple genes from cells seeded in DBMs, should facilitate engineering of scaffolds for tissue repair.
https://v2.sherpa.ac.uk/id/publication/41517?template=romeo
Keywords: Bioluminiscencia; Materiales biomédicos; Células - Diferenciación; In vivo bioluminescence; Cell differentiation; Biomaterials; Demineralized bone matrix